Quality of early childcare in the home and cognitive development at age 5: results from the South African birth to Twenty Plus cohort study. Issue 8 (11th June 2022) - Slemming, Wiedaad; Cele, Refiloe; Richter, Linda M.
ABSTRACT: This study, using longitudinal data from the South African Birth to Twenty Plus study, assessed associations between early childcare quality in the home between six months and two years, household SES and cognitive development at age 5. Childcare quality was assessed using measures of maternal responsiveness and cognitive stimulation. Cognitive development at age 5 was assessed using the Revised Denver Pre-screening Developmental Questionnaire (R-DPDQ). Bivariate analysis and multiple linear regressions were conducted. The analytical sample comprised 856 mother–child pairs. Quality of care in the home differed significantly according to SES status, with more children in the low SES group receiving low quality of care. There was no association between childcare quality and cognitive development. There were differences in the cognitive development scores of children in different socio-economic groups; high levels of cognitive stimulation in the home were associated with increased R-DPDQ scores for children in the low SES group.